The Expression Pattern of p120-Catenin is Associated With Acquired Resistance to Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors in Non–Small Cell Lung Cancer. Issue 1 (January 2018) - Liu, Yang; Wang, Si; Dong, Qian-Ze; Liu, Nan; Han, Yong; Zhang, Xiu-Peng; Fan, Chui-Feng; Wang, En-Hua
Abstract : Background: Previous research connects p120-catenin (p120ctn) with epidermal growth factor receptor (EGFR) signaling pathways, which presents a potential role for p120ctn in EGFR tyrosine kinase inhibitor (EGFR-TKIs) resistance. However, a direct correlation between the expression pattern of p120ctn in solid tumors and the therapeutic effect of EGFR-TKIs has not yet been demonstrated. Methods and Results: In this study, the expression pattern of p120ctn was examined in patients with the EGFR gene mutation in lung adenocarcinoma, and p120ctn was found to have different patterns of expression even in the same mutation type. The therapeutic effect of EGFR-TKIs was investigated in these patients, and patients with an abnormal expression of p120ctn were found to be more likely to have drug resistance. A gefitinib-resistant lung cancer cell line was established and alterations in the p120ctn expression pattern were also observed in vitro. Conclusions: Therefore, this study demonstrates that the expression pattern of p120ctn is associated with acquired resistance to EGFR-TKIs in lung cancer, providing information toward addressing the problem of drug resistance in patients with non–small cell lung cancer.